THE EFFECTS OF INDIVIDUAL AND THE GROUP STUDY ON ACADEMIC ACHIEVEMENT AND ROLE OF EMPHATIC TENDENCY - (:unkn) unknown (HACETTEPE UNIV, 2013)
The purpose of this study is to investigate effects of individual and group study in multi-media learning environments on students' comprehension of what is being listened/watched. At the same time, the role of students' empathic levels in achievement and its interaction with individual/group study is investigated. For this study, a multimedia-learning environment for 4th grade Turkish class was developed. In the environment, ELVES method was implemented. For the study, while some participants studied the material individually, others studied in groups of four that were formed randomly. According to the results of empathic tendency tests, the participants were grouped as low, middle and high empathic tendency level students. t test indicated that individual study improved achievement more than group study did in multimedia learning environments. To investigate the role of empathic tendency, analysis of variance was conducted. The results showed that the high empathic tendency group over-achieved other students in individual study condition. In group study condition, there was not statistically important difference among students with different levels of empathic tendency and similar tendencies were found in both individual and group study conditions. The results showed no significant interaction between empathic tendency level and study type.
Keywords: multimedia; individual vs group study; emphatic tendency; EMPATHY